Trade union strategy in fashion retail in Italy and the USA: Converging divergence between institutions and mobilization?. (December 2019) - Gasparri, Stefano; Ikeler, Peter; Fullin, Giovanna
We investigate trade union strategies in fashion retail, a sector with endemic low wages, precarity and a representation gap. Unions in Milan organized 'zero-hours contract' workers, while their counterparts in New York established an alternative channel of representation, the Retail Action Project. We argue, first, that the dynamics of both cases are counterintuitive, displaying institution-building in the USA and grassroots mobilization in Italy; second, union identity stands out as a key revitalizing factor, since only those unions with a broad working-class orientation could provide an effective representation for fashion retail workers.